Study on multicomponent composite anti-corrosion cement slurry system suitable for ultra-high temperature acid gas wells - Zhang, Yihang; Huang, Yang (Frontiers in Energy Research, 2023)
In the field of oil cementing, corrosion has always been a major problem that perplexes researchers. In the past, the research mainly focused on solving the corrosion problem of cement stone with temperature below 150°C, and there was a lack of corrosion research cases for ultra-high temperature. In addition, the gas channeling problem in the cementing of ultra-high temperature acid gas wells cannot be ignored, which further increases the difficulty in the design of anti-corrosion cement slurry system. Therefore, from the perspective of anti-corrosion, gas channeling and high temperature resistance, this paper uses hydroxyapatite blast furnace slag and functional temperature resistant and anti-corrosion composite emulsion as anti-corrosion additives to build a multi-component composite ultra-high temperature anti-corrosion cement slurry system with good engineering performance and a density range of 1.9 g/cm3-2.4 g/cm3, and analyzes its microstructure and phase composition. The corrosion inhibition mechanism of multicomponent composite cement paste was discussed.